Utilization of Archaeological Excavation Results as a Source of History Learning for History Education Students at the Faculty of Teacher Training and Education, Banda Naira University - Fadli Fatotnem; Rahma Temarwut; Kasman Renyaan (Historia, 2027)
Modern developments demand innovative, contextual, and empirically based history learning. The problem in this research is the suboptimal utilization of archaeological sites and excavations as sources for history learning, despite the abundant potential of historical remains in the surrounding campus. This study aims to describe the utilization of archaeological excavations as sources for history learning and their impact on student learning. The study employed a qualitative descriptive approach using field observation, interviews, and documentation techniques. Observations were conducted at the Gunung Manangis Cave Site and the Okamakatita Site. The results showed that excavation activities increased student enthusiasm and made history learning more concrete and meaningful. Students were directly involved in the process of locating, sorting, and recording findings in the form of artifacts such as ceramic shards, pottery, obsidian, bone, and metal. The utilization of archaeological excavations has been proven to develop critical thinking skills, primary source analysis, and historical awareness, thus warranting a systematic inventory in the history education curriculum at universities.